Data and code for "High-throughput characterization of transition metal dichalcogenide alloys: Thermodynamic stability and electronic band alignment" - Linderälv, Christopher; Rahm, J. Magnus; Erhart, Paul (Chalmers University of Technology, 2022)
This record contains data that support the following publication:

High-Throughput Characterization of Transition Metal Dichalcogenide Alloys: Thermodynamic Stability and Electronic Band Alignment
by C. Linderälv, J. M. Rahm, and P. Erhart, Chemistry of Materials 34, 9364 (2022)

The databases directory contains ASE databases in sqlite format with the results of density functional theory (DFT) calculations, which were used for constructing cluster expansion (CE) models using the icet package.

The ces directory contains CE models in icet format.

The example-*.py scripts provide very simple demonstrations for how the databases and CE models can be accessed.
Keywords: Physical Sciences; Fysik